Газета «Вісті Прилуччини» як історичне джерело історії Чернігівщини періоду нацистської окупації (1941–1943) - Кіріченко, О. (Сiверянський лiтопис, 2019)
На основі матеріалів Державного архіву Чернігівської області досліджено видавничу діяльність газети «Вісті Прилуччини» за 1941–1943 рр., схарактеризовано її тематичні рубрики. The publishing activity of the newspaper «Visti Pryluchyny» during 1941-1943 was
researched with the help of materials from the State Archive of Chernihiv region. Also topic
headlines were analyzed.
Chernihiv Oblast was released from Nazi army 76 years ago. This part of the history is still
interesting to the researchers of nowadays. Learning of the press of occupation period gives
us the possibility to study the history of Chernihiv Oblast, events during this period and life
of people. The newspaper «Visti Pryluchyny» was published during 1941–1943 yy. in the city
Pryluky. Editors of the newspaper were F. Kharchenko, D. Pylypenko, V. Klyaznyk. Although
the two last was only like part-time editors. The publication came out three times a week and
it consisted of two pages on Sunday and Friday and four on Wednesday. The reason for
increasing the column was the heading «Literary page» that appeared in December 3, 1941.
The newspaper presented materials about events at the front, in agriculture, as well as articles
that had an anti-Semitic character. The main headings were: «Messages from the Führer’s
House» or «Messages from the German Armed Forces”; «Events devoted to land administration
and agriculture”; «Criticism of the foundations, events, culture, etc. of socialism”; «Message
from the front”; «Invitation to work in Germany”; «Announcement”; «Orders”; «Prose and
Anecdotes”; «Caricature”; «Literary page”; «Our Calendar”; information about the theater
and the cinema; short messages and the rubric «Lost Documents», various photographs of
German leisure, cultural events, science and politics.
We can say that the newspaper «Visty Pryluchyny» fulfilled its information task, supported
and gave hope to the people to continue life. In addition, this edition is an important
additional source for studying the history of Chernihiv region during the German occupation.